Numerical study of the fracturing mechanism around a blasthole and investigating the effect of discontinuities on the fracture pattern: Numerical study of the fracturing mechanism (Rudarsko-geološko-naftni zbornik, 2020)
The mechanism of rock fragmentation around blastholes is of prior importance in the evaluation of drilling and blasting performance in open pit and underground mines. This paper aims to numerically investigate the crack propagation mechanism around a single blasthole using the distinct element method (DEM). In this study, two specimens with different borehole diameters were considered and the effects of the stress waves on their cracking mechanism were simulated. To validate the numerical model, the length of the radial cracks around each blasthole was measured and compared against an analytical fracture mechanics model. The fractured zones around the blasthole were also compared against previous experimental tests and good agreement was observed. The effect of a single discontinuity on the crack propagation mechanism was also studied and it was found that the discontinuity normal stiffness plays a significant role in the fractured zones around the blasthole. For low values of normal stiffness, the discontinuity surface acted as a free surface, and the shock wave was significantly reflected, while at high values of normal stiffness, cracks propagate across the discontinuity surface.